Influence of the economic crisis on the identification of country profiles within the European tomato market - Capobianco-Uriarte, María de las Mercedes; Gázquez-Abad, Juan Carlos; De Pablo-Valenciano, Jaime; Casado-Belmonte, María del Pilar (Journal of Business Economics and Management, 2021)
The objectives of this work are to determine the profiles of the countries that make up the European tomato consuming market and to observe if the economic-financial crisis (2007/2008) has influenced them. Both Lafay’s economic indicators were applied and country profiles and subprofiles were identified through a multilevel two-stage cluster analysis. The empirical analysis covers the period from 2005 to 2016, separated into two periods, pre-crisis (2005–2010) and post-crisis (2011–2016). Most countries obtained import and export profiles that coincide in both indices, Except in Italy. Only one post-crisis profile change was detected, this being for Greece, from an importer to an exporter. As a result of the initial two-stage clustering analysis (both in the pre-crisis and post-crisis period), three clusters were obtained. At the first level of clustering, Italy is identified with a producer profile and Spain and the Netherlands with an exporter profile. At the second level of clustering of the initial larger group, two clusters were identified, Germany and the United Kingdom with an importing sub-profile, and France and Belgium with an exporting sub-profile. In the transition from the pre-crisis to the post-crisis period, Portugal changed from a producer sub-profile to an exporter sub-profile.